Drought alters the carbon footprint of trees in soils—tracking the spatio‐temporal fate of 13C‐labelled assimilates in the soil of an old‐growth pine forest. (19th March 2021) - Gao, Decai; Joseph, Jobin; Werner, Roland A; Brunner, Ivano; Zürcher, Alois; Hug, Christian; Wang, Ao; Zhao, Chunhong; Bai, Edith; Meusburger, Katrin; Gessler, Arthur; Hagedorn, Frank
Abstract: Above and belowground compartments in ecosystems are closely coupled on daily to annual timescales. In mature forests, this interlinkage and how it is impacted by drought is still poorly understood. Here, we pulse‐labelled 100‐year‐old trees with 13 CO2 within a 15‐year‐long irrigation experiment in a naturally dry pine forest to quantify how drought regime affects the transfer and use of assimilates from trees to the rhizosphere and associated microbial communities. It took 4 days until new 13 C‐labelled assimilates were allocated to the rhizosphere. One year later, the 13 C signal of the 3‐h long pulse labelling was still detectable in stem and soil respiration, which provides evidence that parts of the assimilates are stored in trees before they are used for metabolic processes in the rhizosphere. Irrigation removing the natural water stress reduced the mean C residence time from canopy uptake until soil respiration from 89 to 40 days. Moreover, irrigation increased the amount of assimilates transferred to and respired in the soil within the first 10 days by 370%. A small precipitation event rewetting surface soils altered this pattern rapidly and reduced the effect size to +35%. Microbial biomass incorporated 46 ± 5% and 31 ± 7% of the C used in the rhizosphere in the dry control and irrigation treatment respectively. Mapping the spatial distribution of soil‐respired 13 CO2 around the 10 pulse‐labelled trees showed that tree rhizospheres extended laterally 2.8 times beyond tree canopies, implying that there is a strong overlap of the rhizosphere among adjacent trees. Irrigation increased the rhizosphere area by 60%, which gives evidence of a long‐term acclimation of trees and their rhizosphere to the drought regime. The moisture‐sensitive transfer and use of C in the rhizosphere has consequences for C allocation within trees, soil microbial communities and soil carbon storage. Abstract : To quantify the transfer of carbon from tree canopies into the belowground, we conducted a pulse‐labelling with 100‐year old trees in a 15‐year‐long irrigation experiment within a naturally dry pine forest. It took four days until new assimilates were allocated from tree canopies to the rhizosphere. One year later, the 13 C signal of the three‐hour long pulse labelling was still detectable in stem and soil respiration. Mapping the spatial distribution of soil‐respired 13 CO2 around pulse‐labelled trees showed that rhizospheres extended laterally 2.8 times beyond tree canopies. Drought reduced the transfer rates and spatial distribution of assimilates allocated to the soil.